2012
DOI: 10.2196/jmir.1969
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of eHealth Search Perspectives Among Female College Students in the Health Professions Using Q Methodology

Abstract: BackgroundThe current “Millennial Generation” of college students majoring in the health professions has unprecedented access to the Internet. Although some research has been initiated among medical professionals to investigate the cognitive basis for health information searches on the Internet, little is known about Internet search practices among health and medical professional students.ObjectiveTo systematically identify health professional college student perspectives of personal eHealth search practices.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…In other words, a factor was labelled because it was evident in the rankings of the distinguishing items. The overall pattern of the statements helped to understand the views that discriminated the clusters of students (Stellefson, Hanik, Chaney, & Tennant, 2012). It should be noted that 18 of the students (46.1%) had Q-sorts that identified them as hesitant and limited computer access cooperators.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, a factor was labelled because it was evident in the rankings of the distinguishing items. The overall pattern of the statements helped to understand the views that discriminated the clusters of students (Stellefson, Hanik, Chaney, & Tennant, 2012). It should be noted that 18 of the students (46.1%) had Q-sorts that identified them as hesitant and limited computer access cooperators.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that a higher education does not guarantee better Internet skills [36,37] and other studies among higher educated populations confirm these results. For example, Hughes et al [38] showed that doctors often choose their search results based on navigational bias and a focus on what is known, and Stellefson et al [39] found that many health professional college students are rather unconfident when evaluating information from the Internet. Furthermore, a younger age and more Internet experience might enhance operational skills, but previous studies have found that strategic eHealth literacy problems are still frequently present among students who grew up using the Internet [16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…The objective of Q-methodology is neither to uncover cause nor to generalize demographic prevalence of variables to a large population. Hence, a small sample size is quite common and acceptable when utilizing Q-methodology (Brown, 1993;Brown, 1996;Stellefson et al, 2012). The three steps of Q-methodology are as follows: (1) Development of the research instrument: to create a set of statements to be sorted, (2) Data collection: to sort those statements along a continuum of preferences (i.e., from agree to disagree) by each participant, and (3) Data analysis: to analyze and interpret the data (see Figure 3).…”
Section: Measuring Subjectivitymentioning
confidence: 99%